2014
DOI: 10.1021/ol502871r
|View full text |Cite
|
Sign up to set email alerts
|

Base-Mediated Hydroamination of Propargylamine: A Regioselective Intramolecular 5-exo-dig Cycloisomerization en Route to Imidazole-2-thione

Abstract: An intramolecular transition-metal-free base-mediated hydroamination of propargylamine with isothiocyanates has been achieved. This atom-economical, regioselective intramolecular 5-exo-dig cycloisomerization was utilized for the one-pot synthesis of diversely substituted imidazole-2-thione and spiro-cyclic imidazolidine-2-thione. The reaction goes to completion at room temperature via propargylthiourea and 65-97% isolated yields were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…Earlier we reported that, in the presence of base, propargylamine reacts with isothiocyanate, and hydroamination product imidazolidine‐2‐thione 5a is exclusively formed . But under the current optimized solvent‐free conditions, hydrothiolation product thiazolidine 4a was exclusively formed through not isolated propargylthiourea intermediate 3a .…”
Section: Resultsmentioning
confidence: 79%
“…Earlier we reported that, in the presence of base, propargylamine reacts with isothiocyanate, and hydroamination product imidazolidine‐2‐thione 5a is exclusively formed . But under the current optimized solvent‐free conditions, hydrothiolation product thiazolidine 4a was exclusively formed through not isolated propargylthiourea intermediate 3a .…”
Section: Resultsmentioning
confidence: 79%
“…[8] Various nitrogen-and sulfur-containing heterocycles have been synthesized from isothiocyanate substrates. [9] In particular, o-alkynylphenyl isothiocyanates have been used to construct fused-ring compounds via cascade reactions, [10] which show higher overall efficiency than traditional stepwise syntheses because multiple CÀC and CÀX bonds can be formed in one pot. [11] For example, in 2014, Cai et al reported the formation of 5H-benzo [d]imidazo [5,1-b] [1,3]thiazines by means of copper-catalyzed [3 + 2] cascade cycloaddition reactions between o-alkynylphenyl isothiocyanates and isocyanides (Scheme 1a).…”
Section: Abstract: Biologically Active; Copper; Cyclization; Heterocymentioning
confidence: 99%
“…The steric and electronic effects of the phenyl ring substituents on the propargylamine ( 38 ) backbone affected the selectivity of the reaction (Table ). The reaction of compound 38 (R 1 =Ph) with different isothiocyanates ( 35 ) resulted in the imidazole thione derivatives ( 41) as a sole product in moderate yield …”
Section: Synthesis Of Thiazolesmentioning
confidence: 99%